Fungsi Kearifan Lokal dalam Peribahasa Kulawi sebagai Penguat Karakter Etnik Kulawi:Kajian Semiotika - NFN TAMRIN; NFN Yunidar; NFN Nursyamsi; Siti Fatinah (Balai Bahasa Sulawesi Tengah, 2021)
abstractLocal wisdom is one of the products of character strengthening development, both in the form of morals and ethics. Therefore, the meaning of local wisdom can be knitted and developed in shaping the nation's moral and ethical character. By raising the theme of the function of local wisdom in Kulawi proverbs as a reinforcement of the Kulawi ethnic character, this study aims to describe the functions and meanings contained in Kulawi proverbs that show local wisdom and cultural values. The method used in this study is a qualitative research method by describing and analyzing phenomena, events, social activities, attitudes and beliefs of individuals and groups. Furthermore, data collection through and analyzed based on Rolan Bhartes' semiotic elements. The results of the analysis show that the meaning of local wisdom contained in the Kulawi proverb is to elevate the morality of the Kulawi ethnic life and assert itself as a dignified community. The function of local wisdom in the Kulawi proverb is as a tool for controlling social norms, a means of communication and controlling society, as a means of education, and as a tool for maintaining the harmony of religious communities.Keywords: local wisdom, proverbs, ethnicity, culture AbstrakKearifan lokal merupakan salah satu produk pengembangan penguat karakter, baik berupa moral amaupun etika. Oleh karena itu, makna kearifan local dapat dirajut dan dikembangkan dalam membetuk karakter bangsa yang bermoral dan beretika. Dengan mengangkat tema fungsi kearifan lokal dalam peribahasa Kulawi sebagai penguat karakter etnik Kulawi, penelitian ini bertujuan mendeskripsikan fungsi dan makna yang terkandung dalam peribahasa bahasa Kulawi yang menunjukkan kearifan lokal dan nilai budaya. Metode yang digunakan dalam penelitian ini adalah metode penelitian kualitatif dengan mendeskripsikan dan menganalisis fenomena, peristiwa, aktivitas sosial, sikap dan kepercayaan individual dan kelompok. Selanjutnya, pengumpulan data melalui dan dianalisis berdasarkan elemen semiotika Rolan Bhartes. Hasil analisis menunjukkan bahwa makna keraifan local yang terdapat dalam peribahasa bahasa Kulawi yaitu meninggikan moralitas kehidupan etnik Kulawi serta menegaskan diri sebagai komunitas yang bermartabat. Adapun fungsi kerifan local dalam peribahasa Kulawi yaitu sebagai alat pengedali norma social, alat komunikasi dan pengedali masyarakat, sebagai sarana pendidikan, dan sebagai alat pemelihara ketrukunan ummat beragama.